Preliminary data on the occurrence of marine turtles in the Laje de Santos Marine State Park (SP, Brazil) - Luchetta, Ana Carolina [UNESP]; Watanabe, Luciana Erika Yaginuma (FapUNIFESP (SciELO), 2017)
Although marine turtles have always been observed by divers, there are few scientific works on marine turtles in the Laje de Santos Marine State Park (PEMLS). Diurnal (bimonthly) and nocturnal (biannual) surveys were conducted between 2013 and 2015 for a more comprehensive study, totalizing 42 hours of diurnal observations and the capture of 41 turtles during nocturnal dives. During the diurnal surveys, visual observations were made from two land based sites (Paredão da Face Sul and Portinho). The numbers of heads (heads observed whether they are of the same turtle or not) and turtles (individuals observed in groups) were counted. The results showed the presence of marine turtles throughout the year. More turtles were observed from Paredão da Face Sul than from Portinho, the latter being a more sheltered point and a site preferred by divers. The nocturnal surveys consisted of the capture of turtles through scuba diving so they could be measured and weighed and tagged according to the guide-lines of the TAMAR project. Four nocturnal surveys were conducted and in the last survey three tagged turtles were captured, two of them having been tagged during this study. The measurements of these turtles indicated their growth during the study period.The present survey also highlighted the importance of the PEMLS as a feeding area for juvenile marine turtles.
Keywords: Biometry; Capture and recapture; Laje de Santos; Land based survey; Marine turtle; Observation